Histopathology and genotoxicity alterations in high Andean catfishes from the Upper Orinoco River Basin, Colombia - W. Corredor-Santamaría; J. P. Alvarez-Silva; M. A. Pérez-Mayorga; Y. M. Velasco-Santamaría; C. A. Roa-Fuentes; A. J. Espinosa-Ramírez (Brazilian Journal of Biology, 2025)
Abstract Freshwater ecosystem pollution has motivated an extensive list of studies due to deleterious impacts becoming a threat to aquatic organisms that inhabit these environments. This is the first approach to water pollution impact derived from human activities on native ichthyofauna in the Garagoa river basin in Boyacá (Colombian Andes). Therefore, the aim of the present study was to evaluate the occurrence of mercury and arsenic in catfishes and armored catfishes from the Garagoa River basin and the presence of hepatic alterations and genotoxicity in peripheral blood. Biomarkers of effect were analyzed in fishes caught in eight tributaries from Garagoa river basin. The increased presence of lesions in the hepatic architecture and nuclear abnormalities in peripheral blood erythrocytes in Dolichancistrus fuesslii, Chaetostoma joropo, Astroblepus latidens and Trichomycterus cf. knerii individuals could be associated with exposure of pollutants. The tissue alterations observed compromise the fish health, due to the biotransformation processes of xenobiotics such as mercury and arsenic and probably other contaminants. We need to increase surveillance in the Garagoa River to ensure ecological health, recognize hematological and tissue effects in native fishes, and develop effective monitoring strategies to mitigate sources of pollution.